Чешская доля: иллюзии и реальности (полемика Милана Кундеры и Вацлава Гавела) - Задорожнюк, Элла Григорьевна (Wydawnictwo Nauka i Innowacje, 2014)
The article is devoted to the analysis of the M. Kundera and V. Havel polemics over the fate and fortunes of the Czech ethnical identity, Czechoslovakian nationhood and ways of Czechoslovakian society development after the August, 1968. This polemic, together with the Prague Spring reflection, caused broad resonance, and some of its statements are still timely. The acceptability of the paradox of Havel being a spokesman of „the Czech lot” while at the same time being its critic in the polemic was proven.
The Czech Lot: Illusions and Realities [Milan Kundera and Václav Havel Polemics]
Keywords: the Czech lot; the Czech question; the Prague Spring; small nation; ethnical identity; dissidents; socialism with human face; regime of normalization